Sharia Qualification and Financial Expertise as Determinants of Islamic Bank Performance - Abdurrahman, Zahron; Putri, Baiq Krisnina Maharani (LifeSciFi, 2025)
Islamic banks rely on Sharia Supervisory Boards, whose religious and financial expertise is essential for ensuring compliance, effective governance, and enhanced financial performance.This study aims to examine the effect of Sharia qualification and financial expertise of Sharia Supervisory Board members on the financial performance of Islamic banks worldwide. Using panel data of Islamic banks from 2019–2023, this research investigates how the dual competencies of Sharia Supervisory Board members religious and financial shape the effectiveness of Sharia governance and influence bank performance measured by Return on Assets and Return on Equity. The study employs panel data regression analysis with a binary scoring system based on AAOIFI and IFSB standards. The results indicate that both Sharia qualification and financial expertise have a positive and significant effect on financial performance, suggesting that competent Sharia Supervisory Board contribute not only to compliance assurance but also to managerial efficiency. These findings enrich the growing body of literature on Sharia governance effectiveness, offering empirical insights from emerging Islamic banking markets. Furthermore, this study provides policy implications for regulators and Islamic financial institutions to strengthen the selection, training, and certification of Sharia Supervisory Board members, thereby improving the quality and structure of Islamic governance.